2020
DOI: 10.24127/ajpm.v9i3.3027
|View full text |Cite
|
Sign up to set email alerts
|

Game Android "MENALAR" Berbasis Adobe Animation CC

Abstract: Penelitian ini bertujuan untuk menghasilkan media pembelajaran jarak jauh dengan menggunakan Adobe Animation CC yaitu berupa permainan edukasi "MENALAR" yang dapat dimainkan di smartphone. Produk dikembangkan dengan memperhatikan aspek validitas, kepraktisan, dan keefektifan dalam pembelajaran matematika pada siswa kelas X SMA Negeri 5 Balikpapan. Adapun implementasinya menggunakan desain pengembangan MDLC yang terdiri dari: (1) konsep, (2) perancangan, (3) pengumpulan materi, (4) pembuatan, (5) pengujian, dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
6
0
3
Order By: Relevance
“…It is related to Sanjaya (2013), which states that repetition, practice, and reinforcement are efforts to strengthen mastery of the lesson. In addition, Pratama (2022) explained that games can create different experiences for students, so this experience makes students' memories of the material presented in games last longer compared to conventional learning. So, it can be concluded that this chemistry ludo game of android-based media effectively reinforces students' concepts so that learning outcomes increase.…”
Section: Hypothesis Testmentioning
confidence: 99%
“…It is related to Sanjaya (2013), which states that repetition, practice, and reinforcement are efforts to strengthen mastery of the lesson. In addition, Pratama (2022) explained that games can create different experiences for students, so this experience makes students' memories of the material presented in games last longer compared to conventional learning. So, it can be concluded that this chemistry ludo game of android-based media effectively reinforces students' concepts so that learning outcomes increase.…”
Section: Hypothesis Testmentioning
confidence: 99%
“…Penelitian tentang pengembangan game edukasi telah dibahas oleh beberapa peneliti (Abdullah & Yunianta, 2018;Alexander et al, 2018;Fahlevi & Yuliani, 2021;Firdaus & Yermiandhoko, 2020;Jayanti et al, 2022;Mubharokh dkk, 2021;Parsianti dkk, 2020;Permatasari dkk, 2022;Pratama, & Waskitoningtyas, 2020;Putri et al, 2020;Wati & Istiqomah, 2019;Winarni et al, 2020). Contohnya penelitian terkait game edukasi "Menalar" oleh Pratama & Waskitoningtyas (2020) dengan hasil game edukasi valid dan praktis digunakan dalam pembelajaran matematika, serta nilai belajar meningkat ketika menjawab soal-soal permasalahan bab trigonometri SMP dan PLTV SMA. Kemudian, produk game edukasi "Cermat" oleh Fahlevi & Yuliani (2021) dengan hasil game edukasi valid dan praktis digunakan pada materi geometri, serta meningkatkan keterampilan siswa SMA dalam menyelesaikan soal problem solving.…”
Section: Pendahuluanunclassified
“…Oleh sebab itu, peneliti dapat menyimpulkan keseluruhan bahwa game edukasi yang dihasilkan valid, praktis, dan efektif diterapkan ketikam mengajarkan matematika. Kesimpulan sama dengan pengamatan pengembangan game edukasi oleh (Abdullah & Yunianta, 2018;Alexander et al, 2018;Fahlevi & Yuliani, 2021;Firdaus & Yermiandhoko, 2020;Hapsari & Fahmi, 2021;Haryadi & Andriati, 2020;Kartikasari & Rahmawati, 2018;Mubharokh dkk, 2021;Parsianti dkk., 2020;Permatasari dkk, 2022;Pratama & Waskitoningtyas, 2020). Contonya pengembangan game edukasi "Menalar" oleh Pratama & Waskitoningtyas (2020) didapatkan hasil game edukasi valid, efektif, dan praktis digunakan untuk bertambahnya nilai pada permasalahan trigonometri SMP dan persamaan linear tiga variabel SMA.…”
Section: Hasil Penelitian Dan Pembahasanunclassified
“…This application is part of Adobe graphics and publishing software that can be used to do web design and create interactive HTML animations (Rizkiya, 2019). There are several studies that have used this application to develop educational games such as the research of Sarji et al, (2022) who developed an algebra adventure media based on educational games, Setiawan et al (2022) who developed interactive multimedia on the material of rows and series, and also the study of Pratama & Waskitoningtyas (2020) and Kurniawan et al (2022) which developed a reasoning android game and trigonometry educational game development, respectively. Just as the Titungan board game has been proven to train creative thinking skills, the development of the Titungan game is expected to train creative thinking.…”
Section: Introductionmentioning
confidence: 99%